From belonging to success: Evaluating the influence of sense of belonging to physics on first-year university students’ academic outcomes and the benefits of a holistic support program - Feser, Markus Sebastian; Bauer, Anna Brigitte (European Journal of Physics)
Abstract The present study explored the role of first-year physics students’ sense of belonging to physics and how it relates to their learning progression in higher education-level physics. Conducted at Paderborn University, this study examined how students’ sense of belonging to physics influences their academic outcomes in an introductory experimental physics course. Additionally, we investigated how physics students’ engagement in the Physiktreff—a holistic support program for first-year physics students to help them cope with academic and social challenges during their studies—impacts the development of their sense of belonging to physics over time. Our findings indicated that students with a stronger sense of belonging to physics performed better academically. Moreover, students who actively participated in the support program experienced a positive shift in their sense of belonging to physics. However, our findings also revealed that physics students with a higher initial sense of belonging to physics tended to experience a decline in their sense of belonging to physics during their first semester. These results underscore the importance of fostering a sense of belonging to physics within higher education, particularly during the introductory phase of students’ studies.

Protecting physics students from pseudoscience - combining strategies for a comprehensive teaching approach - Webersen, Yvonne; Riese, Josef (European Journal of Physics)
Abstract Given the presence of fake news and pseudoscience (often disguised as physics), the importance of inoculating citizens against this type of misinformation has gained increasing attention in education. This is a goal that all subjects should pursue equally from their respective disciplinary perspectives. The paper presents a teaching approach to protect physics students from misinformation and pseudoscience by combining these three common strategies: First, understanding the fundamental principles of the Nature of Science. Second, identifying techniques of Science Denial. And third, applying heuristics for evaluating (supposedly) scientific information. Finally, the paper offers practical suggestions for applying these strategies in a master's-level physics course, using examples from the field of physics.

Calculating the distributions of number, mass and luminosity of the stars with the help of MS Excel - Hohmann, Sascha (European Journal of Physics)
Abstract Astrophysical topics can be treated with the methods of different areas of physics, mathematics and other natural sciences. The integration of these topics into such areas could improve students’ motivation and strengthen the connections between different fields of the mentioned sciences. In this article, an example of the connection between the physics of the stars and that of their statistical distributions is given. The usage of Microsoft Excel simplifies the mathematical requirements and gives the possibility of seeing the changes of distribution with the growing age of the regarded population of stars. The changes are a direct consequence to the limited lifetime of the stars and the limited age of the considered population of stars.
Keywords: General Physics and Astronomy

Excitons with anisotropic effective mass - Schindlmayr, Arno (European Journal of Physics)
We present a simple analytic scheme for calculating the binding energy of excitons in semiconductors that takes full account of the existing anisotropy in the effective mass, as a complement to the qualitative treatment in most textbooks. Results obtained for excitons in gallium nitride form the basis for a discussion of the accuracy of this approach.